2012
DOI: 10.1039/c2fo10245e
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of angiotensin I converting enzyme by subtilisin NAT (nattokinase) in natto, a Japanese traditional fermented food

Abstract: Angiotensin I converting enzyme (ACE) was inhibited by the culture medium of Bacillus subtilis subsp. natto, which ferments boiled soy beans to natto, a Japanese traditional food. Subtilisin NAT (nattokinase) produced by B. subtilis also inhibited ACE, and the inhibition was markedly stimulated by heat treatment of subtilisin at 120 °C for 15 min. Inhibition of ACE by subtilisin was of a mixed type: the decrease in V(max) and the increase in K(m) value. SDS-polyacrylamide gel electrophoresis showed that heat t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 14 publications
(21 reference statements)
0
24
0
Order By: Relevance
“…Fermented milk has been reported to lower BP in humans [29,30]; however, a recent meta-analysis found that fermented milk, which was expected to lower BP through lactobacillus fermentation, had no such effect [31]. Murakami et al [32] reported that angiotensin-converting enzyme was inhibited by subtilisin nattokinase in natto, a Japanese traditional fermented food [32]. …”
Section: Discussionmentioning
confidence: 99%
“…Fermented milk has been reported to lower BP in humans [29,30]; however, a recent meta-analysis found that fermented milk, which was expected to lower BP through lactobacillus fermentation, had no such effect [31]. Murakami et al [32] reported that angiotensin-converting enzyme was inhibited by subtilisin nattokinase in natto, a Japanese traditional fermented food [32]. …”
Section: Discussionmentioning
confidence: 99%
“…Vitamin K 1 , the most abundant form found in an individual’s diet [ 115 ], is high in green leafy cruciferous vegetables, fruits, various vegetable oils and beans [ 114 ]. Vitamin K 2 , the more bioavailable form of vitamin K [ 114 ], comes in a variety of fish, offal, meat, dairy products, fermented cheese (e.g., blue cheese), and fermented products like natto (fermented soybeans, a Japanese delicacy) [ 116 ].…”
Section: Vitamin Kmentioning
confidence: 99%
“…The type of microorganism involved in the fermentation process plays a key role in the fermentation process. Bacillus subtilis has been used as a starter strain for manufacturing soybean fermented products with potential antihypertensive, antithrombotic and fibrinolytic properties (Murakami, Yamanaka, Ohnishi, Fukayama, & Yoshino, 2012;Omura, Hitosugi, Zhu, Ikeda, & Maeda, 2005). Recently, Dueñas et al (2012) have reported that B. subtilis enhance the production of isoflavone aglycones, thus improving the antioxidant activity of fermented soybean.…”
Section: Introductionmentioning
confidence: 98%